First Records of Several Tanypodinae Species (Diptera, Chironomidae) from Ukraine - Baranov, V.A. (Вестник зоологии, 2013)
Three species of Tanypodinae: Conchapelopia melanops (Meigen, 1818), Paramerina cf. cingulata (Walker, 1856), Procladius (Psilotanypus) flavifrons Edwards, 1929 are recorded for the first time for Ukraine. Notes on morphology of P. cf. cingulata are given. Три вида Tanypodinae Conchapelopia melanops (Meigen, 1818), Paramerina cf cingulata (Walker, 1856), Procladius (Psilotanypus) flavifrons Edwards, 1929 указаны впервые для Украины. Даны комментарии по поводу странной морфологи крыла P. cf. cingulata.